2006
DOI: 10.1136/jech.2005.041954
|View full text |Cite
|
Sign up to set email alerts
|

Global health inequalities: an international comparison

Abstract: Objective: To study cross-national inequalities in mortality of adults and of children aged ,5 years using a novel approach, with clustering techniques to stratify countries into mortality groups (better-off, worse-off, mid-level) and to examine risk factors associated with inequality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(52 citation statements)
references
References 16 publications
0
52
0
Order By: Relevance
“…There are few studies that explore global health inequalities using cluster analysis 6 20. Our study offers a far greater stratification of countries with which to summarise these inequalities than previous studies but also validates the clustering of countries into 12 groups through comparing countries’ life expectancies and health system indicators.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are few studies that explore global health inequalities using cluster analysis 6 20. Our study offers a far greater stratification of countries with which to summarise these inequalities than previous studies but also validates the clustering of countries into 12 groups through comparing countries’ life expectancies and health system indicators.…”
Section: Discussionmentioning
confidence: 99%
“…Novel approaches to geo-demographic classification using cluster techniques have recently emerged in the study of health inequalities in the USA, the UK and internationally 46. This last study considered international inequalities in mortality in adults and children, with nation-states stratified into three mortality groups (better-off, mid-level and worse-off) and by risk factors associated with health inequality.…”
mentioning
confidence: 99%
“…This includes those countries and regions where there are the highest rates of mortality and morbidity. A recent study of 207 countries found that among the countries in the group with high adult and child mortality, all were in Sub-Saharan Africa (SSA) with the exception of Afghanistan (Ruger & Kim, 2006). Progress in health in many SSA countries has stagnated, and there have even been reversals in progress.…”
Section: The Principlesmentioning
confidence: 98%
“…Addressing such disparities could be pursued through a social response that involves a commitment to expanding human capability for health, that is, a person's ability to achieve good health and their real opportunities to live the life they choose (Ruger, 2004;Sen, 1992). Individuals should have the capability to be healthy regardless of where they live in the world (Ruger, 2006).…”
Section: The Principlesmentioning
confidence: 99%
“…This inverted relationship between good-health and poverty has been observed across and within countries (Marmot, 2005, Ruger et al 2006, Whitehead, 2001) and is particularly true for water-related diseases. Indeed, poorer people living in riskier environments and with riskier life-styles (CSDH, 2005) have a higher burden of water-related diseases.…”
Section: Water and Sanitation Water-related Diseases And Povertymentioning
confidence: 99%